2004
DOI: 10.1002/hep.20012
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of pioglitazone treatment for nonalcoholic steatohepatitis† ‡

Abstract: Nonalcoholic steatohepatitis (NASH) is a common chronic liver disease for which there is no known effective therapy. A proportion of patients with NASH progress to advanced fibrosis and cirrhosis. NASH is considered one of the clinical features of the metabolic syndrome in which insulin resistance plays a central role. This prospective study evaluates the role of insulin-sensitizing agent in treatment of NASH. Eighteen nondiabetic patients with biopsyproven NASH were treated with pioglitazone (30 mg daily) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
435
1
18

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 676 publications
(470 citation statements)
references
References 33 publications
16
435
1
18
Order By: Relevance
“…22,27 In the PIVENS trial the change in ballooning score was significantly higher with pioglitazone. 26 Intralobular inflammation improved in most 22,26,27,30 but not all 21 studies. Portal inflammation was either unchanged or worse in one study with rosiglitazone.…”
Section: Efficacy Outcomesmentioning
confidence: 96%
See 4 more Smart Citations
“…22,27 In the PIVENS trial the change in ballooning score was significantly higher with pioglitazone. 26 Intralobular inflammation improved in most 22,26,27,30 but not all 21 studies. Portal inflammation was either unchanged or worse in one study with rosiglitazone.…”
Section: Efficacy Outcomesmentioning
confidence: 96%
“…26 Fibrosis. No studies convincingly demonstrated improvement in fibrosis: despite an end-of-treatment reduction 22,27,30 there was no statistical difference with the comparator arm, or only a marginal level suggestive of type 1 error. 27 When measured by micromorphometry, a more sensitive and quantitative technique, there was still no significant improvement, even after prolonged treatment with rosiglitazone.…”
Section: Efficacy Outcomesmentioning
confidence: 97%
See 3 more Smart Citations